Quantifying the impact of higher capital requirements on the Swiss economy - Georg Junge; Peter Kugler (University of Basel, Center of Business and Economics (WWZ), 2012)
So far the discussion in Switzerland about the social costs and benefits of higher capital requirements resulting from the new Basel III Accord and the Swiss Too Big To Fail legislation has been heavily qualitative. This paper provides a quantitative view and estimates the long-run costs and benefits of substantially higher capital requirements using empirical evidence on Swiss banks to assess both benefits and costs. The analysis yields two main conclusions. The long-run economic benefits of higher capital requirements are substantial for the Swiss economy leading to a significantly lower probability of banking crises and associated expected losses. In contrast the costs of higher capital requirements as reflected in increased lending spreads and potential output reductions are literally non-existent. As an aside we note that the cyclical component of leverage is a major driver of leverage in the banking sector. This suggests that macro-prudential measures such as the countercyclical buffer could be an important tool against the build-up of systemic banking crises.
Keywords: G21; G28; 330; Capital regulation; banks; cost of equity; banking crisis; economic growth; Modigliani-Miller; Basler Akkord; Kapitalkosten; Bankenkrise; Wirtschaftswachstum; Kapitalstrukturtheorie; Schweiz